Films, Tangos and Cultural Practices - Young, Richard (Cinémas, 1996)
Although first associated with the urban culture of Buenos Aires in the early part of this century, tango has become internationalized and has acquired meanings that permit it to be understood in other contexts. In particular, since the time of Valentino, it has become accommodated to the international cinema, where it is viewed not only as a cultural practice that expresses desire and sensuality, but as a sign that generates its meaning in part from other signs and other manifestations of the same sign. Beginning therefore with a consideration of cultural practice as repetition and variation, this paper will comment on several films in which tango is not only used as a motif but relies for our understanding of it on other contexts and sometimes other films in which tango has appeared.